Persistent high postoperative carcinoembryonic antigen in colorectal cancer patients- is it important? - Ali Ilker Filiz (Clinics, 2009)
INTRODUCTION: Evaluation of pre- and postoperative serum CEA levels together has seldom been assessed for the prognosis of colorectal cancer (CRC). OBJECTIVE: To concurrently evaluate pre- and postoperative CEA as factors of relapse and survival. METHODS: The study consisted of 114 patients who had undergone surgery from February 2002 to June 2006 for CRC. All patients were classified into four groups according to their pre- and postoperative CEA levels. Data obtained for clinicopathologic parameters, lymph node metastasis, stage, recurrence, and CEA levels were analyzed to determine their association with survival. Multivariate analysis by the Cox proportional hazard regression model was performed to identify the independent prognostic factors associated with survival. RESULTS: Postoperative serum CEA levels remained high in Group 3 (n = 32). Nineteen patients (59.3%) demonstrated a detectable cause for persistent high CEA levels, while the reasons for those in the other thirteen patients (40.6%) remained obscure. Abnormal preoperative CEA levels significantly correlated with the depth of tumor invasion, lymph node metastasis, TNM stage, and recurrence (p < 0.05). Abnormal postoperative CEA levels were significantly related to the depth of tumor invasion, TNM stage, and postoperative relapse (p<0.05). Patients in Group 3 demonstrated the worst survival rate. Abnormal postoperative CEA levels, lymph node metastasis, and location of the tumor were independent prognostic factors for survival. CONCLUSION: The survival of patients with high postoperative CEA levels due to unknown reasons may be extended if they are exhaustively tested with sensitive diagnostic methods and treated at an early stage.